Improved percutaneous delivery of some NSAIDs for the treatment of arthritis - Rushabh Thosani; Vijay Pawar; Rajani Giridhar; Mange Ram Yadav (Wolters Kluwer Medknow Publications, 2012)
Arthritis is a heterogeneous group of conditions that leads to joint symptoms and signs which are associated with defective integrity of articular cartilage. Major classes of drugs which are widely used for the treatment of arthritis are Non-Steroidal Anti-inflammatory Drugs (NSAIDs). Development of an efficient means of percutaneous delivery can increase drug concentration in local soft-tissues and joints while reducing the systemic distribution of a drug and its side effects. The present work is aimed at synthesisand evaluation of prodrugs of some NSAIDs for percutaneous drug delivery for the treatment of arthritis.